Zrzeczenie się spółdzielczego prawa do lokalu - Stecki, Leopold (Wydział Prawa i Administracji UAM, 1988)
A renouncement of a right to cooperative premises by a member of a housing cooperative in favour of that cooperative may take place due to various reasons and in various circumstances. Although Polish law on cooperative societies does not regulate the institution of a renouncement of a right in favour of a cooperative, such an act should be considered possible. It may pertain to a property-like right to a cooperative apartment, to a tenancy-like right to a cooperative apartment as well as to a right to cooperative business premises. A renouncement of a right to cooperative premises is a dispositional legal transaction causally involving increment of property, usually for a valuable consideration. A declaration to renounce such a right should be issued in a written form (ad probationem). Taking up the premises by a member of a cooperative is not a prerequisite for a renouncement of that right. The object of a renouncement is the right, not the premises. The said act may concern either a right to premises only, or that right together with the share in a cooperative society. A member cannot renounce a part of that right or a part of his/her apartment. In principle, only a member of a cooperative may renouncet that right. Exceptions concern the member's heirs and legatees since they may renounce the right without being members of a housing cooperative. One of the spouses may renounce the said right only when that right belongs to his/her separate property If the right belongs to a common matrimonial property, one of the spouses may renounce that right only if the consent of the other spouse has been granted. In the case of so-called independent common property with respect to a right to a cooperative apartment, the declarations of will of both spouses are necessary. In consequence of a renouncement, a right to cooperative premises expires. However, the relationship of membership in a cooperative remains intact. Two different situations should be distinguished. The first appears when a member renounces the said right just because he/she wants to get rid of that right and he/she wants the cooperative to grant that right to another person. The second situation takes place when the renouncement of that right is a part of a contract for exchange of an apartment concluded with a cooperative. The said contract needs to be properly qualified. A tendency to subsume it under Art. 603 and 604 of the Civil Code, regulating the exchange contract, is understandable, yet one should also keep in mind that here the object of exchange are not things but rights and that on the part of a member a transfer of a right does not take place since the right expires in consequence of a renouncement. In turn, a cooperative society creates a new right to a new apartment in favour of that member. Thus its act has no features of a translative transmission of a right. In practice, such an act leads eventually to the exchange of cooperative apartments. Thus one might assume that in such a case a "sui generis" contract for allocation of another right to premises, or — simplifying a little — a contract for exchange of a coperative apartment comes into existence.
Renouncement of a right to premises in a housing cooperative